A participatory assessment of nitrified urine fertilizer use in Swayimane, South Africa: Crop production potential, farmer attitudes and smallholder challenges - Wilde, Benjamin C.; Lieberherr, Eva; Pereira, Engil; Odindo, Alfred; Six, Johan (Frontiers in Sustainable Food Systems, 2022)
Long-term nutrient mining of soil hampers agricultural production across Africa. However, emerging sanitation technologies afford a hygienically safe and ecologically sustainable solution to this development challenge by providing fertilizers derived from human excreta that could facilitate a socio-technical transition towards a more sustainable food system. To evaluate one such technology, nitrified urine fertilizer (NUF), we conducted participatory action research to assess the potential, from both a biophysical and social perspective, of NUF to serve as a soil fertilizer to support smallholder agricultural production in Swayimane, South Africa. To achieve this objective, we formed a stakeholder group comprised of a cooperative of smallholder farmers, a local NGO (Zimele), and researchers from ETH Zurich and the University of Kwazulu-Natal. Over the course of two growing seasons (2016 and 2017) this stakeholder group assessed the potential of NUF to support smallholder vegetable production (i.e. cabbage). First, we adopted a randomized complete block design incorporating five treatments in season 1 (unfertilized control, nitrified urine, nitrified urine+bone meal, urea, and urea+diammonium phosphate (DAP) and six treatments (unfertilized control, urea, urea+DAP, DAP, nitrified urine, and nitrified urine+DAP) in season 2 to assess cabbage yield and leaf nutrient concentration (sodium, phosphorus, potassium, carbon, nitrogen). Although we observed large variability in yields, the urine-based treatments were as effective as any of the chemical fertilizers. Second, beyond the biophysical analysis, we elicited the challenges and opportunities of the smallholder farmers in our stakeholder group, as well as their attitudes toward the use of NUF as a fertilizer. Through this qualitative work, farmers indicated that their attitudes about the use of NUF as a fertilizer improved and that they would be willing to incorporate this product into their production practices if it was available at scale. Thus, we demonstrate the potential of participatory action research to co-produce knowledge and awareness around an innovative technology. In so doing, we provide evidence that this approach can support a change toward nutrient recycling-based agriculture.